EFEK SUBSTITUSI PERTUMBUHAN PINJAMAN PEER-TO-PEER (P2P) TERHADAP PERTUMBUHAN KREDIT BANK KONVENSIONAL DI INDONESIA - Kohardinata, Cliff; Widianingsih, Luky Patricia (JURNAL LENTERA AKUNTANSI, 2023)
Peer-to-peer (P2P) platforms have developed rapidly in the financial industry in Indonesia. The rapid P2P Platform influences the banking sector in Indonesia so that it is important to examine the effect of P2P loan growth on banking credit growth from various perspectives to gain a deeper understanding. This study aims to examine the effect of peer-to-peer (P2P) loan growth on the credit growth performance of conventional banks in Indonesia from July 2019 to March 2020 using data from 33 provinces in Indonesia. The results of this study indicate that P2P loan growth has a significant negative effect on overall banking credit growth.Key words: P2P, peer-to-peer, Fintech, Banking Credit, Loan